Analisis Tata Kelola Teknologi Informasi untuk Mendefinisikan Proses TI pada STIE 45 Mataram Menggunakan Framework COBIT 4.1 - Nadiyasari Agitha; Nabhan Rabbani; Sri Endang Anjarwani (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
STIE 45 Mataram is in the stage of implementing information technology in achieving the existing vision and mission. But there are problems such as the absence of a special section that controls the management of information technology, the lack of staff who are skilled in the IT field and the responsibility for each IT team member who is not yet organized. Therefore, a guide is needed to help resolve this problem, which is in this study uses the COBIT 4.1 Framework. The selected IT process attributes are PO4 and AI7. The average attribute condition is currently at maturity level 2. The expected condition is at maturity level 4 except the attribute SE in PO4 which is at maturity level 5. The recommendations are given in the form of steps to increase the maturity level, form an action plan equipped with an implementation schedule and estimated time that can be run.